Does hybridization with an invasive species threaten Europe’s most endangered reptile? Genomic assessment of Aeolian lizards on Vulcano island - Josephine R. Paris; Gentile Francesco Ficetola; Joan Ferrer Obiol; Iolanda Silva-Rocha; Miguel Angel Carretero; Daniele Salvi (iScience)
Summary: Interspecific hybridization can be consequential for insular species. The Critically Endangered Aeolian wall lizard, Podarcis raffonei, severely declined due to interactions with the invasive Italian wall lizard, Podarcis siculus. The largest population of P. raffonei survives on a narrow peninsula (Capo Grosso) that is mildly connected to the island of Vulcano, which has been entirely invaded by P. siculus. Recent observation of individuals with an intermediate phenotype raised concern over the risk that hybridization might swamp this last stronghold. We genetically characterized lizards from Vulcano, considering individuals showing multiple phenotypes (native, invasive, and “intermediate”). Hybridization rate was low (∼3%), with just two F1 hybrids and two backcrosses, suggesting that hybridization does not currently represent a major threat. However, we identified low genetic diversity, a small effective population size, and a low Ne/Nc ratio. Management strategies are urgently needed to control invasive species and maintain the genetic diversity of P. raffonei.